Experimental investigation of pile characteristics of non-spherical particles mixtures: pile height and angle of repose. Issue 1 (1st June 2022) - Widartiningsih, P M; Putra, M I R; Aji, D P P; Rudiawan, A N F; Viridi, S
Abstract: An angle of repose is defined as the steepest angle of a conical pile that is naturally formed when a bulk of particulate solid is poured onto a flat surface. It has been considered as one of the important properties in characterizing granular material due to its effectiveness in determining flowability of granular, pile profile in an opaque container, and granular transportation system. Since the angle of repose is sensitive to the shape of individual particles, investigations through experiments and simulations for various forms of particles have been carried out. However, most of them were performed under homogeneous particle systems. While in practical situations, granular mixtures consisting of a variety of particle shapes are commonly employed. This study presents an experimental investigation of angles of repose resulting from a mixture of two types of non-spherical particles with different values of roundness. Experiments have been carried out with different compositions and have been repeated five times to ensure their reproducibility. The results show that the angle of repose linearly corresponds to the granular composition, where the coefficient of determination is 0.95. Therefore, the effect of granular composition in binary mixtures on the characteristics of the resulting pile has been demonstrated in this study.